Postoperative outcomes of lung transplant recipients with preformed donor-specific antibodies. (22nd December 2020) - Kayawake, Hidenao; Chen-Yoshikawa, Toyofumi F; Gochi, Fumiaki; Tanaka, Satona; Yurugi, Kimiko; Hishida, Rie; Yutaka, Yojiro; Yamada, Yoshito; Ohsumi, Akihiro; Hamaji, Masatsugu; Nakajima, Daisuke; Date, Hiroshi
Abstract: OBJECTIVES: Few studies have evaluated the outcomes of lung transplantation (LTx) in recipients with preformed donor-specific antibodies (DSAs). This study investigated the postoperative changes in preformed DSAs based on prospectively collected data of DSAs, and the influences of preformed DSAs on postoperative outcomes among LTx recipients. METHODS: Between July 2010 and December 2019, 216 recipients underwent LTx (81 living-donor lobar lung transplants and 135 deceased-donor lung transplants). We reviewed 8 cases with preformed DSAs to determine postoperative changes in DSAs and compared postoperative outcomes between recipients with and without DSAs. RESULTS: The preoperative mean fluorescence intensity of preformed DSAs ranged from 1141 to 14 695. Two recipients experienced antibody-mediated rejection within 2 weeks after LTx. DSAs disappeared in 7 recipients; however, 1 recipient experienced the relapse of DSAs and died from chronic lung allograft syndrome (CLAD), whereas 1 recipient had persisting DSAs within the study period and died from CLAD. Neither overall survival (OS) nor CLAD-free survival was significantly different between recipients with and without DSAs ( P = 0.26 and P = 0.17, respectively). However, both OS and CLAD-free survival were significantly lower in recipients with DSAs against HLA class II than in those without these antibodies 5-year OS: 25.0% [95% confidence interval (CI): 0.9–66.5%] vs 72.1% (95% CI: 63.8–78.9%), P = 0.030 and 5-year CLAD-free survival: 26.7% (95% CI: 1.0–68.6%) vs 73.7% (95% CI: 66.5–79.5%), P = 0.002. CONCLUSIONS: Prognosis in recipients experiencing the relapse of preformed DSAs and those with persisting DSAs may be poor. The recipients with anti-HLA class II preformed DSAs had a significantly worse prognosis.